Ex Vivo Stromal Cell-Derived Factor 1-Mediated Differentiation of Mouse Bone Marrow Mesenchymal Stem Cells into Hepatocytes Is Enhanced by Chinese Medicine Yiguanjian Drug-Containing Serum. (14th April 2016) - Fu, Linlin; Pang, Bingyao; Zhu, Ying; Wang, Ling; Leng, Aijing; Chen, Hailong
Abstract : Yiguanjian is administered in traditional Chinese medicine for liver diseases and has been demonstrated to reduce liver fibrosis. This study investigated the effect of Yiguanjian drug-containing serum (YGJ) with Stromal Cell-Derived Factor 1 (SDF-1) and Hepatocyte Growth Factor (HGF) on the differentiation of murine bone-marrow-derived mesenchymal cells (BM-MSCs) into hepatocytes in vitro . Adherent MSCs were isolated from murine bone marrow. Differentiation was induced by 20 ng/mL HGF, 50 ng/mL SDF-1, and 20% Yiguanjian drug-containing serum for 7 to 28 days, and mature hepatocytes' marker albumin (ALB) and cholangiocytes' marker cytokeratin-18 (CK-18) were assessed by immunocytochemistry and western blot. BM-MSCs exhibited homogeneous spindle shape growth after subculture and stained positive for CD90 and negative for CD34. After induction with HGF + normal serum or YGJ for 14 days, HGF + SDF-1 + normal serum for 7 days, or HGF + SDF-1 + YGJ for 5 days, MSCs' morphology changed gradually and begun to resemble hepatocyte-like cells. Cultures supplemented with HGF + SDF-1 + YGJ contained significantly higher proportions of ALB and CK-18 positive cells than cultures supplemented with HGF + SDF-1 + normal serum at day 7. These observations corroborated the results of western blot. In conclusion, Yiguanjian drug-containing serum could facilitate the differentiation of murine BM-MSCs into hepatocytes in vitro and has a synergistic effect with SDF-1 and HGF.